Geographical Indications: Eastern Partnership Countries case - Natalia MOGOL (Eastern European Journal of Regional Studies)
Abstract: In the Eastern Partnership (EaP) countries, the subject of geographical indications is particularly important. Although the approach to the subject of GIs in the EaP countries is uneven and differs from country to country, the attention that each of these states pays at the national level to the field of geographical indications cannot be neglect. In countries such as Georgia and Moldova, the development of the GI system is one of the national strategic objectives. This interest is largely due to those economic benefits offered by the implementation of the geographical indications system, especially in countries where the share of the agri-food sector in GDP is significant. Despite the fact that challenges regarding the implementation of the association agreement in the part concerning geographical indications in the EaP countries are quite similar, there are no complex studies regarding the implementation of the geographical indications systems in the Eastern Partnership Countries. The main purpose of this paper is to fulfill the existing gap and to analyze the current situation in the field of GI highlighting best practices but also the vulnerabilities of the GI system in the EaP countries.